Pola Asuh Ibu dalam Pendidikan Religius Anak: Studi Kasus Perempuan Multi-Agama - Rizal, Syaiful (Al-Riwayah : Jurnal Kependidikan, 2021)
The family has a very important role, because the family as the first place the creation of personality and family is the best field in seeding values the value of religious education for children. The role of a mother is so vital in the religious education of children, for a mother to be a figure close to the child in terms of both social and emotional. This study aims to describe how the role of a mother figure in a multi-faith religious education of rural children. This study uses qualitative-phenomenological method. Subject of research are three families. Data was collected by purposive sampling. The results showed the role of a mother multi Religion in the religious education of children in the village Umbulsari there are four stages, namely: a) Educate with etiquette habituation and Training (Parenting), b) Educate the ketauladanan, c) Educate with advice, and d) Educate with supervision